Impact of AI in Human Resource Management (HRM), Focusing on Recruitment and Selection - Beqiri, Theranda; Beqiri, Gonxhe; Berisha, Vlora (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Integrating Artificial Intelligence (AI) in Human Resource Management (HRM) has transformed traditional HR practices, enhancing efficiency and decision-making through data-driven insights. This study investigates the impact of AI on HRM practices, specifically focusing on its influence on recruitment processes and the barriers faced by job seekers in this evolving landscape. A structured questionnaire was distributed to HR professionals and job seekers across various industries. The questionnaire aimed to assess perceptions of AI's effectiveness in recruitment, its role in decision-making, and the obstacles job seekers encounter when interacting with AI-driven systems. Preliminary results indicate that AI significantly enhances recruitment efficiency by automating candidate sourcing and screening. But it also introduces significant barriers for job seekers, including algorithmic bias, and the impersonal nature of AI interactions. However, challenges such as data privacy concerns and resistance to change were identified. The study concludes that while AI has the potential to revolutionize HRM practices, ethical implications, and accessibility issues must be addressed to create a more inclusive recruitment environment. This research contributes to the growing body of literature on AI in HRM and highlights the importance of balancing technological advancement with equitable recruitment practices.